2012
DOI: 10.1038/eye.2012.224
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic cellular yield is superior with full pars plana vitrectomy compared with core vitreous biopsy

Abstract: Purpose Vitreous biopsy for the cytological assessment of suspected intraocular lymphoma and vitritis of uncertain aetiology is a standard investigation. The types of specimens generated and the diagnostic rate are variable within and between centres. There are many reasons for this but one observation that has not been considered previously is the differential distribution of cells in the vitreous gel. To test this possibility, five consecutive patients with suspected vitreous involvement by lymphoma or vitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 10 publications
0
28
0
1
Order By: Relevance
“…First, a larger number of cells can be collected. Mudhar et al reported that the lymphoma cells were concentrated more in the cortical vitreous than core vitreous 10. Additionally, Conlon et al reported that vitrectomy did not cause any more cellular degradation than simple aspiration 11.…”
Section: Discussionmentioning
confidence: 99%
“…First, a larger number of cells can be collected. Mudhar et al reported that the lymphoma cells were concentrated more in the cortical vitreous than core vitreous 10. Additionally, Conlon et al reported that vitrectomy did not cause any more cellular degradation than simple aspiration 11.…”
Section: Discussionmentioning
confidence: 99%
“…It is also helpful for obtaining the GoldmannWitmer quotient. Cytology and fl ow cytometry, even with such small samples, can be helpful for diagnosis [ 24 ]. Case series of diagnostic vitrectomies reported yields from 30 to 81.6 % [ 25 ].…”
Section: Diagnosticmentioning
confidence: 97%
“…Apart from allowing the visualization of the fundus and allowing better diffusion of intraocular medications, the vitrectomy also has the advantage of yielding more samples with enough material available for multiple tests. Studies have also shown a better yield from samples which have been obtained closer to the retina, theorizing that these cells may be more viable compared to the more distal cells [ 24 ].…”
Section: Technique For Vitreous Samplingmentioning
confidence: 97%
“…5,11,44 Diagnostic cellular yield is superior with full pars plana vitrectomy compared with core vitreous biopsy. 56 The gold standard remains the cytopathologic examination. However, immunophenotyping, flow cytometry, and molecular analysis are helpful to improve the diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%